Kerk en burgerlike owerheid: Die Nederlandse geloofsbelydenis en drie kerkordes - Strauss, Piet J. (HTS teologiese studies, 2021)
Church and state authorithy: The Confessio Belgica and three church orders. In reformed churches the Bible is regarded as the norm of the norms. The confessions of faith of these churches are the second norm and subjected to the Bible. The church order is less powerful than the Bible and the confessions but of a higher status than the normal decisions of church assemblies. Therefore, the influence of the Belgic Confession on three church orders is an important issue in these churches.The author recommends four principles to understand the relation between the church and the state authority in article 36 of the Belgic Confession: both should honour God in their activities; both are guided by the Ten Commandments; both have their own internal law to fulfil the purpose as an institution; and both should respect and co-operate with one another. Although they are not in agreement on every aspect, these principles give the guidance to understand the main issue in all four documents which are investigated. The theme of this article is of a theological and church historical nature and a contribution on a well-discussed topic in reformed churches.Contribution: It should be important for the reformed churches in the Dutch tradition that a dynamic relationship exists between their confessions of faith and their church orders. While the Bible is the first and most important norm for church life, the confessions are the second most important. Church history shows that the relationship between the church and state is of utmost importance for the church, the quality of the confessions and the order of the church.